Effects of Molybdenum application on nutrient uptake and yield of rice and Nitrogenase activity of Rhizobacteria - Zakikhani, Hamed (2016)
In tropical soils, the deficiency of Mo may be seen in the rice plants. Hence, elucidating the optimum levels of Mo in soil and plants will be helpful for understanding the plant growth. The current study was conducted to assess Mo status in soils and plants, and to determine the influences of Mo on in vitro nitrogenase activities of some plant growth promoting rihizobacteria (PGPR). Five rice cultivars (MR219, HASHEMI, MR232, FAJRE and MR253) and 4 levels of Mo (0, 0.01, 0.1, and 1.0 mg L−1) were used for the first experiment. The highest Mo uptake in shoots (0.70 μg plant-1) and roots (0.66 μg plant-1) were seen in the MR232 at the highest level of Mo (1 mg L-1) in solution culture. Iron rates in shoot decreased with increasing Mo levels in solution culture and reached 39.93 μg plant-1 at the highest level of Mo. Also, phosphorus uptake in all cultivars increased with enhancing Mo in medium culture and reached highest (0.6 %) in cultivar MR232. In other experiment, Mo combination (0, 0.01, 0.05, 0.1, 0.5, 1, 1.5, 2, 2.5 mg L-1) was applied to the growth medium contained four nitrogen fixation bacteria (UPMB10, UPMB12, Sb16 and R19). Nitrogenase activity enhanced with increasing Mo levels in growth medium of all bacteria strains except Sb16. The strongest correlation (r =0.78**, p˂0.01) was found between Mo and ethylene production in UPB10, and the weakest one was seen in R19 (r =0.49*, p˂0.05). The highest ethylene productions in UPMB10 (99.6 μmol mol-1 hour-1), UPMB12 (87.2 μmol mol-1 hour-1) and R19 (80.1 μmol mol-1 hour-1) were seen in treatments contained 2.5 ppm Mo. We collected eleven soil series from two depths of Kedah and Kelantan paddy fields. Sequential extractions of soil Mo fractions indicated that Kranji series contained highest plant available amount of Mo (0.26 mg kg-1) in comparison with other seven series of Kedah soils (surface layer), and highest medium plant available Mo (0.24mg kg-1) was seen in Rotan and Sedaka series of Kedah area (surface layer). In upper layers of Kedah soil series, we could not detect any acid soluble Mo (associated with calcium). In surface layers of Kelantan, highest amount of plant available Mo (0.23 mg kg-1) was found in in Lating series but medium plant available of Mo (0.15 mg kg-1) was obtained from Cempaka series. In lower depths of Kedah, Guar series contained highest plant available mount of Mo (0.28 mg kg-1) and medium plant available rate of Mo (0.35 mg kg-1) was seen in Rotan series. In lower layers of Kelantan, Lating series contained highest amount of plant available Mo (0.34 mg kg-1) and medium plant available of Mo rate (0.07 mg kg-1) was only found in Batu Hitam series. We found out that cation exchange capacity was positively correlated with total amount of Mo in upper layers of Kedah soil series (r= 0.61; P ≤ 0.05), and no statistically correlation was found between Mo contents and soil properties in Kelantan soil series. For the last experiment, we used foliar and soil application methods in order to determine the optimum Mo rate at which highest rice grain is produced. We found out that grain yield of rice was correlated with total shoot dry weight and plant height with r value of 0.53* and 0.74* in treatments sprayed with Mo. The greatest grain yield (21 g plant-1) was seen in treatment of 5 mg Mo kg-1 in soil, and treatment of 30 μg Mo L-1 supplied as foliar.